2017
DOI: 10.18823/asiatefl.2017.14.3.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Improving Grammatical Accuracy in Thai Learners' Writing : Comparing Direct and Indirect Written Corrective Feedback

Abstract: Written corrective feedback (WCF) is widely used to point students to the grammatical errors in their written work and help reduce them. This paper reports a quasi-experimental study that compared the effectiveness of direct and indirect teacher WCF in a Thai context. One hundred and twenty Thai students at two public universities in southern Thailand were assigned to write argumentative essays within a treatment period; each treatment had 60 students. The feedback was given by four ESL/EFL lecturers at the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
(55 reference statements)
4
24
3
Order By: Relevance
“…Furthermore, in contrast with the positive findings for WCF, a study by Truscott and Hsu (2008) that compared the texts of writers who received and did not receive WCF and by tracing their accuracy improvement over time, has indicated an opposite finding. Despite the inconclusiveness of its effectiveness, WCF is used in varying forms and degrees in formal classroom instructions (Tan & Manochphinyo, 2017). Furthermore, argued that the effectiveness of WCF must be measured over time to investigate its retention effect by incorporating delayed pot-test.…”
Section: Inconclusive Evidence On Written Corrective Feedbackmentioning
confidence: 99%
“…Furthermore, in contrast with the positive findings for WCF, a study by Truscott and Hsu (2008) that compared the texts of writers who received and did not receive WCF and by tracing their accuracy improvement over time, has indicated an opposite finding. Despite the inconclusiveness of its effectiveness, WCF is used in varying forms and degrees in formal classroom instructions (Tan & Manochphinyo, 2017). Furthermore, argued that the effectiveness of WCF must be measured over time to investigate its retention effect by incorporating delayed pot-test.…”
Section: Inconclusive Evidence On Written Corrective Feedbackmentioning
confidence: 99%
“…Jeong (2010) compared the effect of a peer-feedback group to a non-feedback group using computermediated communication and found that peer feedback produced meaningful revisions and provided students with the opportunities to learn from their peers and negotiate meaning with each other. Students become more autonomous and produce higher quality compositions when using corrective feedback strategies (Cassidy & Bailey, 2018;Han, 2012;Tan & Manochphinyo, 2017;Wooley et al, 2008). Wooley et al (2008) hypothesized that students who provided peer feedback on specific dimensions of writing during peer review would "lead to stronger cognitive organization for reviewers which, in turn, would translate to stronger writing of their own" (p. 2378).…”
Section: Categorizations Of L2 Writing Strategiesmentioning
confidence: 99%
“…While the first one designed the contents based on the genre-based approach, the other focused on the writing of an argumentative essay (Expository) and its structure. Tan and Manochphinyo (2017) argued that intensive training prior to the feedback activity is essential. Even though training was made in the present study, the training focused mainly on the essay writing structure and feedback types.…”
Section: Intensive Training Is Importantmentioning
confidence: 99%